2020
DOI: 10.1007/s00259-020-04992-8
|View full text |Cite
|
Sign up to set email alerts
|

Thyroglobulin doubling time offers a better threshold than thyroglobulin level for selecting optimal candidates to undergo localizing [18F]FDG PET/CT in non-iodine avid differentiated thyroid carcinoma

Abstract: Purpose To investigate the potential role of serum thyroglobulin doubling time (TgDT) in predicting 2-deoxy-2-[ 18 F]fluoro-Dglucose ([ 18 F]FDG) PET/CT results in patients affected by differentiated thyroid carcinoma (DTC) who demonstrated a combination of positive Tg but a negative [ 131 I] whole-body scan ([ 131 I]-WBS). Materials and methods Inclusion criteria were (1) prior [ 131 I] treatment for DTC, (2) negative subsequent [ 131 I]-WBS, (3) no interfering anti-Tg antibodies, (4) three consecutive Tg mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 26 publications
(31 reference statements)
0
14
0
1
Order By: Relevance
“…The hypothesis of a connection between Tg kinetics and PET detection rate is logical and based on the idea that an aggressive and rapidly growing tumor should have a greater metabolic activity and is more likely to be FDG-avid. The effective usefulness of Tg kinetics in predicting PET/CT results is not completely understood with promising papers [21,22]. Giovanella et al [21] demonstrated that the accuracy of 2-[ 18 F]-FDG PET/CT was significantly higher in patients with unstimulated Tg above 5.5 ng/mL and the TgDT below 1 year.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The hypothesis of a connection between Tg kinetics and PET detection rate is logical and based on the idea that an aggressive and rapidly growing tumor should have a greater metabolic activity and is more likely to be FDG-avid. The effective usefulness of Tg kinetics in predicting PET/CT results is not completely understood with promising papers [21,22]. Giovanella et al [21] demonstrated that the accuracy of 2-[ 18 F]-FDG PET/CT was significantly higher in patients with unstimulated Tg above 5.5 ng/mL and the TgDT below 1 year.…”
Section: Discussionmentioning
confidence: 99%
“…Giovanella et al [21] demonstrated that the accuracy of 2-[ 18 F]-FDG PET/CT was significantly higher in patients with unstimulated Tg above 5.5 ng/mL and the TgDT below 1 year. A recent study [22] showed the superiority of TgDT using a threshold of 2.5 years compared to Tg as absolute value.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To identify an [ 18 F]FDG-PET/CT indication for PD detection, serum Tg level before RAI therapy is a well-established parameter [ 19 , 20 ]. In a recent study, the diagnostic performance of PET/CT for PRD detection was significantly improved by Tg doubling time with an optimal threshold of 2.5 years in DTC patients with negative IWBS findings [ 21 ]. However, serum Tg levels could be influenced by several factors such as serum TgAb level and TSH stimulation methods [ 22 ].…”
Section: Discussionmentioning
confidence: 99%